Penerapan Metode Jigsaw Untuk Meningkatkan Motivasi Dan Hasil Belajar Ipa Materi Daur Air Semester II Pada Siswa Kelas V SD NEGERI I TANJUNGAN TAHUN 2021/2022 - Sri Temuningsih (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
This research aims to improve the learning process for science subjects for fifth grade students at SD Negeri 1 Tanjungan. The research results obtained from the first cycle showed that in the first cycle there had been an increase in understanding of learning but had not been able to understand the material on adapting plants to their environment. This can be seen from the results achieved in the formative test in cycle I, there are still students who have not mastered the material, it is proven that there are still 5 students who have not finished studying, the score is less than 63 with a percentage of 25% so cycle II needs to be implemented. In cycle II, an increase in student learning outcomes was seen. This means that improving learning in cycle II can increase students' understanding by revealing learning material. In the results of the analysis of learning improvements in cycle II, an average score of 90% was obtained, meaning it can be concluded that from cycle I to cycle II there was success. The conclusion is that by using concrete objects there is an increase in the quality of the process and the ability to understand the adaptation of plants to their environment.